Determination of Salmonella enterica Leaf Internalization Varies Substantially According to the Method and Conditions Used to Assess Bacterial Localization - Chahar, Madhvi; Kroupitski, Yulia; Gollop, Rachel; Belausov, Eduard; Melotto, Maeli; Sela-Saldinger, Shlomo (Frontiers in Microbiology, 2021)
In a previous study, comparing the internalization of S. enterica serovar Typhimurium in various leaves by confocal microscopy, we have demonstrated that the pathogen failed to internalize tomato leaves. Numerous reasons may account for these findings, yet one such factor might be the methodology employed to quantify leaf internalization. To this end, we have systematically studied leaf localization of a Green-fluorescent protein-labeled Salmonella strain in tomato, lettuce, and Arabidopsis leaves by surface sterilization and enumeration of the surviving bacteria, side by side, with confocal microscopy observations. Leaf sterilization was performed using either sodium hypochlorite, silver nitrate, or ethanol for 1 to 7min. The level of internalization varied according to the type of disinfectant used for surface sterilization and the treatment time. Treatment of tomato leaves with 70% ethanol for up to 7min suggested possible internalization of Salmonella, while confocal microscopy showed no internalization. In the case of in lettuce and Arabidopsis leaves, both the plate-count technique and confocal microscopy demonstrated considerable Salmonella internalization thought different sterilization conditions resulted in variations in the internalization levels. Our findings highlighted the dependency of the internalization results on the specific disinfection protocol used to determine bacterial localization. The results underscore the importance of confocal microscopy in validating a particular surface sterilization protocol whenever a new pair of bacterial strain and plant cultivar is studied.